Brain microbleeds, anticoagulation, and hemorrhage risk: Meta-analysis in stroke patients with AF. (5th December 2017) - Charidimou, Andreas; Karayiannis, Christopher; Song, Tae-Jin; Orken, Dilek Necioglu; Thijs, Vincent; Lemmens, Robin; Kim, Jinkwon; Goh, Su Mei; Phan, Thanh G.; Soufan, Cathy; Chandra, Ronil V.; Slater, Lee-Anne; et al.
Abstract : Objectives: To assess the association between cerebral microbleeds (CMBs) and future spontaneous intracerebral hemorrhage (ICH) risk in ischemic stroke patients with nonvalvular atrial fibrillation (AF) taking oral anticoagulants. Methods: This was a meta-analysis of cohort studies with >50 patients with recent ischemic stroke and documented AF, brain MRI at baseline, long-term oral anticoagulation treatment, and ≥6 months of follow-up. Authors provided summary-level data on stroke outcomes stratified by CMB status. We estimated pooled annualized ICH and ischemic stroke rates from Poisson regression. We calculated odds ratios (ORs) of ICH by CMB presence/absence, ≥5 CMBs, and CMB topography (strictly lobar, mixed, and strictly deep) using random-effects models. Results: We established an international collaboration and pooled data from 8 centers including 1, 552 patients. The crude CMB prevalence was 30% and 7% for ≥5 CMBs. Baseline CMB presence (vs no CMB) was associated with ICH during follow-up (OR 2.68, 95% confidence interval [CI] 1.19–6.01, p = 0.017). Presence of ≥5 CMB was related to higher future ICH risk (OR 5.50, 95% CI 2.07–14.66, p = 0.001). The pooled annual ICH incidence increased from 0.30% (95% CI 0.04–0.55) among CMB-negative patients to 0.81% (95% CI 0.17–1.45) in CMB-positive patients ( p = 0.01) and 2.48% (95% CI 1.2–6.2) in patients with ≥5 CMBs ( p = 0.001). There was no association between CMBs and recurrent ischemic stroke. Conclusions: The presence of CMB on MRI and the dichotomized cutoff of ≥5 CMBs might identify subgroups of ischemic stroke patients with AF with high ICH risk and after further validation could help in risk stratification, in anticoagulation decisions, and in guiding randomized trials and ongoing large observational studies.